The mediating role of workplace milieu resources on the relationship between emotional intelligence and burnout among leaders in social care - Anna Kozák; Réka Schutzmann; Klára Soltész-Várhelyi; Fruzsina Albert (PLoS ONE, 2025)
Background This study investigated the connection between emotional intelligence and burnout through the mediating role of workplace milieu resources (a sense of community and mutual trust between employees) among social care leaders in Hungary utilizing the Job Demand-Resources model as a reference. The study evaluated emotional intelligence across three dimensions: understanding our emotions, understanding others’ emotions, and positive emotional appraisal. Methods A cross-sectional and quantitative study was conducted from 11th April to 30th November 2019 targeting Hungarian social care leaders. Participants (N = 547) were recruited non-randomly trough a training organized for them. Data collection involved sociodemographic questions, the Assessing Emotions Scale and the Copenhagen Psychosocial Questionnaire. Descriptive statistics, Pearson’s correlation, and three saturated serial mediations (ML with percentile bootstrap) were implemented. During the mediations, one dimension of emotional intelligence was used as a predictor in each model with the sense of community and mutual trust as serial mediators, and burnout as the outcome. Results The results confirmed the role of the leader’s emotional intelligence in creating a supportive workplace atmosphere and its indirect effect on burnout through these workplace milieu resources, while its direct effect was found not to be substantial. Among the three aspects of emotional intelligence, positive appraisal had the largest effect on burnout. Conclusions This study suggests that emotional intelligence’ influence on burnout is mediated by workplace milieu resources. Therefore, it is crucial to encourage leaders to use their emotional intelligence to create a positive emotional atmosphere rather than solely concentrating on emotional comprehension.